The effects of rapidity of fading on communication systems - Galantucci, B.; Kroos, Christian; Rhodes, T. (John Benjamins Publishing, 2010)
Although rapidity of fading has been long identified as one of the crucial design features of language, little is known about its effects on the design of communication systems. To investigate such effects, we performed an experiment in which pairs of participants developed novel communication systems using media that had different degrees of rapidity of fading. The results of the experiment suggest that rapidity of fading does not affect the pace with which communication systems emerge or the communicative efficacy of the emerged systems. However, rapidity of fading seems to affect the design of these systems. In particular, communication systems implemented in the more rapidly fading medium exhibited a higher degree of combinatorial reuse of their forms than systems implemented in the medium that faded more slowly. These results suggest that the design of language might be constrained by subtle relations the presence of which can be ascertained only through direct experimental manipulation. Human communication systems crafted today in the laboratory can provide new insights into the design of natural languages.